Finding Workers, Offenders, or Students Most at-Risk for Violence: Actuarial Tests save Lives and Resources. Issue 3 (December 2013) - Zagar, Robert John; Kovach, Joseph W.; Basile, Brother Benjamin; Hughes, John Russell; Grove, William M.; Busch, Kenneth G.; Zablocki, Michael; Osnowitz, William; Neuhengen, Jonas; Liu, Yutong; Zagar, Agata Karolina
147 adults (107 men, 40 women) and 89 adolescents (61 boys, 28 girls), selected randomly from referrals and volunteers, were given the Ammons Quick Test (QT), the Beck Suicide Scale (BSS), the Minnesota Multiphasic Personality Inventory Second (MMPI–2) or Adolescent Versions (MMPI–A), the Raven's Advanced Progressive Matrices, and the Standard Predictor (SP) of Violence Potential Adult or Adolescent Versions. The goals were to: (a) demonstrate computer and paper-and-pencil tests correlated; (b) validate tests to identify at-risk for violence; (c) show that identifying at-risk saves lives and resources; and (d) find which industries benefited from testing at-risk. Paper-and-pencil vs. computer test correlations (.83–.99), sensitivity (.97–.98), and specificity (.50–.97) were computed. Testing at-risk saves lives and resources. Critical industries for testing at-risk individuals may include airlines, energy generating industries, insurance, military, nonprofit-religious, prisoners, trucking or port workers, and veterans.